Effects of cyclic longitudinal mechanical strain and dexamethasone on osteogenic differentiation of human bone marrow stromal cells - Jagodzinski M.; Drescher M.; Zeichen J.; Hankemeier S.; Krettek C.; Bosch U.; van Griensven M. (European Cells & Materials, 2004)
The aim of the study was to investigate the effect of cyclic mechanical strain on differentiation markers in the presence or absence of dexamethasone. Human bone marrow stromal cells (BMSC) from seven donors (32.5±6.2 years) were cultivated with (D+) or without (D-) dexamethasone. A cyclic mechanical strain with an elongation of 2% (D+2; D-2) or 8% (D+8; D-8) was applied for three days with a stimulation time of three times two hours each day. Levels of alkaline phosphatase (ALP) and osteocalcin (OC) were compared after time intervals of four and seven days. mRNA expression of Collagen I, III and Cbfa1 was investigated after one, four, and seven days. ALP levels were significantly increased in the D+8 group after four and seven days (147.1±6.3%; p<0.05 and 168.6±6,5%; p<0.03) and in the D-8 group after 7 days (197.4±10.4; p<0.04). Cyclic strain had a significant influence on ALP-secretion (F=7.5; p<0.01). In the D-8 group there was a significant increase in OC secretion after 4 days (140.9±12.5%; p<0.05).; p<0.01). The effect of stretching was significantly stronger than that of dexamethasone (F=17.2 vs. 1.8). Collagen I (Col I) expression was upregulated in D+8 cultures after 4 days (215.0±53.3 p<0.04) and after seven days (166.7±55.7; p<0.04). Collagen III (Col III) expression was upregulated in D+2 and D+8 cultures after 4 days (200.7±16.3 and 185.9±12.7; p<0.04) and after seven days (154.4±10.1 and 118.8±16.4; p<0.04). There was a significant increase of Cbfa1 expression in D+8 cultures at all investigated time intervals (day 1: 105.5±3.7%; day 4: 104.7±3.0%; day 7: 104.4±2.1%; p<0.03). Stretching (F=20.0; p<0.01) was a stronger contributor to Cbfa-1 expression than dexamethasone (F=12.1; p<0.01). Cyclical mechanical stimulation with 8% elongation increases ALP and OC levels and upregulates Col I and III synthesis and Cbfa1 expression. In the short term, cyclical stretching is a stronger differentiation factor than dexamethasone. Cyclical stretching and dexamethasone both enhance the osteogenic commitment of hBMSC.